PENGETAHUAN ETIKA AKUNTANSI, RELIGIUSITAS DAN LOVE OF MONEY SEBAGAI DETERMINAN PERSEPSI ETIS MAHASISWA AKUNTANSI - Lestari, Baiq; Permatasari, Ditya (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
This study aims to determine the perceptions of accounting students, about the influence of ethical knowledge, religiosity, and love of money from Islamic-based university.This research used quantitative research. The technique of data analysis that used to test the hypothesis is simple and multiple regression analysis sample in this study were 151 respondents.Data were collected using a questionnaire.The results of this study indicate that Ethical Knowledge and Religiosity have a positive effect on the Ethical Perceptions of Accounting Students.While Love of Money had a negative effect on the Ethical Perceptions of Accounting Students.From the results of the simultaneous test of Ethics Knowledge, Religiosity, and Love of Money on Ethical Perception of Accounting Students has a simultaneous effect. The higher level of the understanding of their religion, so the level of their money more less than before, vice versa.